Confocal μ -XANES as a tool to analyze Fe oxidation state in heterogeneous samples: the case of melt inclusions in olivine from the Hekla volcano - R. Botcharnikov; M. Wilke; J. Garrevoet; M. Portnyagin; K. Klimm; S. Buhre; S. Krasheninnikov; R. Almeev; S. Moune; G. Falkenberg (European Journal of Mineralogy, 2024)
Here we present a confocal Fe K-edge μ -XANES method (where XANES stands for X-ray absorption near-edge spectroscopy) for the analysis of Fe oxidation state in heterogeneous and one-side-polished samples. The new technique allows for an analysis of small volumes with high spatial 3D resolution of <100 µ m 3 . The probed volume is restricted to that just beneath the surface of the exposed object. This protocol avoids contamination of the signal by the host material and minimizes self-absorption effects. This technique has been tested on a set of experimental glasses with a wide range of Fe 3+ / <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="fb147fccdcf98a9911cf3d26a8f6dc33"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-195-2024-ie00001.svg" width="8pt" height="14pt" src="ejm-36-195-2024-ie00001.png"/></svg:svg> Σ Fe ratios. The method was applied to the analysis of natural melt inclusions trapped in forsteritic to fayalitic olivine crystals of the Hekla volcano, Iceland. Our measurements reveal changes in Fe 3+ / <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="165b352473919034209a9d51d0eaf41d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-195-2024-ie00002.svg" width="8pt" height="14pt" src="ejm-36-195-2024-ie00002.png"/></svg:svg> Σ Fe from 0.17 in basaltic up to 0.45 in dacitic melts, whereas the magnetite–ilmenite equilibrium shows redox conditions with Fe 3+ / <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="539a58614ea8688159b8effbc6d3da8d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-195-2024-ie00003.svg" width="8pt" height="14pt" src="ejm-36-195-2024-ie00003.png"/></svg:svg> Σ Fe ≤0.20 (close to FMQ, fayalite–magnetite–quartz redox equilibrium) along the ...